A Socialism for the Twenty-First Century : Towards the 'Full and Free Development of Every Individual' - Smith, Tony (Historical Materialism Book Series, 2025)
Marx called for a society where the ruling principle is 'the full and free development of every individual.' Capitalism neither is nor can be such a society. Domination, worsening ecological crises, and many other pathologies are its intrinsic features-not bugs that can be corrected. But is there truly a better way to organize society? And if we can imagine one, can we be confident it could be put into practice? The answer to both questions is an emphatic 'Yes!' This book makes the case. It describes in detail a workable model of republican socialism , a vision of socialism worth fighting for.